Five shakespearean songs (1939) For medium voice and piano - FINDLAY, Stuart (Boosey & Hawkes, 1949)
How sweet the moonlightnThe current that with gentle murmur glidesnI was a lover and his lassnThe poor soul sat sighingnUnder the greenwood tree